Electronic structure and vibrational assignments of 2, 5-bis[4-(n-cyclobutyldiaminomethyl)phenyl]furan. (10th September 2020) - Yadav, Sanjai Kumar; Yadav, Garima; Yadava, Umesh
Abstract: Several DNA minor groove binders exhibit numerous therapeutic applications. The crystal structure demonstrating 2, 5-bis[4-(N-cyclobutyldiaminomethyl)phenyl]furan binding within the minor groove of DNA has been reported by Simpson et al (2000 Bioorg. Med. Chem. Lett. 10 2593). In the present study, computational investigations on the title compound have been carried out which comprise geometry optimization, HOMO-LUMO, dipole moment, Molecular electrostatic potential(MEP), thermodynamic parameters, and IR assignments using the B3LYP/6-31G** method. The true minimum was long-established by the nonappearance of negative wavenumbers. A comparison of optimized parameters with crystallographic structure demonstrates slight variations in the conformations of the cyclobutyl groups. A small HOMO-LUMO gap indicates the high chemical reactivity and inter molecule charge transferability. The vibrational spectra of the molecule calculated in 400–3800 cm −1 region, reproduce reliable IR assignments. Bearing in mind the high pharmaceutical significance of minor groove binders and a variety of flexible options accessible for lead optimization will be a bountiful ground for the development of drugs targeting minor grooves.